Terminology of modern media linguistics in interdisciplinary contacts - Syzonov, Dmytro (Current issues of Ukrainian linguistics: theory and practice, 2023)
The article substantiates the thesis about the interdisciplinary nature of media linguistics as an innovative field of modern knowledge. Therefore, media linguistics is an interdisciplinary humanitarian discipline that studies the functional potential of language means in mass communication. The research potential of neoscience is described and systematized in an "Media Linguistics: Dictionary of Terms and Concepts" (Kyiv, 2013) innovative lexicographic edition, which gave an impetus to analyze the terminology of the modern neo-direction through the prism of ten years. Among the perspective tasks, the authors note the interpretation of language as a instrumentality for modeling information and influencing public opinion, taking into account the challenges of the information age, studying unexpected angles of analysis of linguistic and stylistic resources in the media, etc. A separate task is the formation and analysis of the media-linguistic terminology in the context of the diffuseness of modern humanitarian knowledge.As for every innovative science, the development and description of a terminological system, which must correspond to logic, integrity, monosemacy, clarity, motivation, and relevance, remains problematic for media linguistics. The complexity of this process, as stated in the article, is revealed due to the syncretic relationships of the analyzed terminology system with other, tangential to it, fields – psychology, sociology, cultural studies, law, cybernetics, social communications, etc. On the material of media dictionaries not only of Ukrainian, but also of Polish, German and English languages, the author analyzed the terms and concepts in the specified interdisciplinary contacts, which allows to prove the integral nature of media linguistics and determine its place in the system of modern sciences of the socio-humanitarian block.
Keywords: media linguistics; innovative linguistics; media lexicography; term system; integrity of science; neophilology.